“Sie sagen skål und Herre gud und arrivederci”: On the Multilingual Correspondence between Ellen Thesleff and Gordon Craig - Lönnroth, Harry (University of Illinois Press, 2016)
The Finnish painter Ellen Thesleff (1869 − 1954) is one of the most famous female painters in Scandinavian art history. During her stay in Florence, Italy, at the beginning of the twentieth century, she became acquainted with the British theater personality and artist (Edward) Gordon Craig (1872 − 1966). Their correspondence from the first half of the century is a part of European cultural history and art criticism; they write, among other things, about painting and graphics, literature and theater. Of linguistic importance is that the original letters preserved for posterity contain traces of many European languages: not only German, which is a central language in the correspondence, but also French, Italian, and English. The focus of this paper is the coexistence of languages in the multilingual correspondence—about 200 dated and 60 undated letters—kept at the National Library of France in Paris. In this paper, microfilms are used instead of the original material, and the selection of letters is limited to twenty-five. The particular interest lies in Ellen Thesleff as a multiliterate, writing individual, and her choices of and switches between different languages. My study shows that Thesleff used a variety of languages when writing letters. This can, for example, be seen from the perspective of the personal nature and the communicative function of the personal letters, where the “self” of the writer is present. In a way, multilingualism has among other things an emotional function for her: one could, for instance, argue that it was used as a kind of “secret writing” or language play between Thesleff and Craig.
Keywords: multilingual correspondence; code-switching; Ellen Thesleff; Gordon Craig; Pohjoismaiset kielet